Acrokeratosis verruciformis of Hopf: A rare presentation in a young Indian female—A case report and review - Gyanendra Singh; Parth Goswami; Yashdeep Pathania; Tarang Pate (Journal of Family Medicine and Primary Care)
Acrokeratosis verruciformis of Hopf (AVH) is a rare dermatological disorder associated with keratotic lesions primarily on the dorsal surfaces of the hands and feet, caused by a missense mutation in the ATP2A2 gene. Here, we report the case of a 24-year-old woman presenting with multiple wart-like lesions on the hands, feet, and neck over four years. A V-shaped notch on the nails indicated nail dystrophy. The patient had no family history of similar symptoms and an unremarkable medical history. The histopathological examination of a skin biopsy revealed marked hyperkeratosis, acanthosis, papillomatosis, and church spire-like epidermal elevations, confirming the diagnosis of AVH. AVH poses diagnostic challenges due to its similarity to other conditions, such as seborrheic keratosis, lichen planus, and Darier disease. Despite resource limitations precluding genetic testing, thorough clinical and histopathological evaluations were crucial for accurate diagnosis. This case underscores the importance of awareness and documentation of AVH, particularly in nonfamilial cases, to facilitate early recognition and management. Increased vigilance among dermatologists is essential to prevent misdiagnosis and to manage this rare condition effectively.